2017
DOI: 10.1096/fj.201600944rr
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and coordinated single‐molecular interactions at TM4SF5‐enriched microdomains guide invasive behaviors in 2‐ and 3‐dimensional environments

Abstract: Membrane proteins sense extracellular cues and transduce intracellular signaling to coordinate directionality and speed during cellular migration. They are often localized to specific regions, as with lipid rafts or tetraspanin-enriched microdomains; however, the dynamic interactions of tetraspanins with diverse receptors within tetraspanin-enriched microdomains on cellular surfaces remain largely unexplored. Here, we investigated effects of tetraspan(in) TM4SF5 (transmembrane 4 L6 family member 5)-enriched mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 23 publications
1
48
0
Order By: Relevance
“…Recently, we have shown that TM4SF5 forms a protein complex with EGFR and integrin α 5 at the leading membrane edges [6]; dynamic intra-TERM protein associations and translocations during cell migration depend on interactions mong TM4SF5, EGFR, and integrin α 5 at the leading membrane edges of migratory cells to steer migration. These interactions transduce differential synergistic signals in 2-dimensional (2D) and 3-dimensional (3D) culture systems and determine the directional migration.…”
Section: Tm4sf5-enriched Microdomain (T5erm) and Cell Migration Prmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we have shown that TM4SF5 forms a protein complex with EGFR and integrin α 5 at the leading membrane edges [6]; dynamic intra-TERM protein associations and translocations during cell migration depend on interactions mong TM4SF5, EGFR, and integrin α 5 at the leading membrane edges of migratory cells to steer migration. These interactions transduce differential synergistic signals in 2-dimensional (2D) and 3-dimensional (3D) culture systems and determine the directional migration.…”
Section: Tm4sf5-enriched Microdomain (T5erm) and Cell Migration Prmentioning
confidence: 99%
“…Overexpression of promigratory TM4SF5 results in an internalization of CD63 to late lysosomal membranes and prevents the inhibitory effect of CD63 on migration by presumably removing it from the cell surface [9]. Therefore, TM4SF5 expression can modulate localizations of other membrane receptors like CD63 [9], EGFR, or integrin α 5 [6], although its effects on CD44 localization have not been examined. Finally, the interaction among TM4SF5, integrin α 2 [10], and α 5 can modulate cell migration, invasion, and vascular endothelial growth factor (VEGF) expression.…”
Section: Tm4sf5-enriched Microdomain (T5erm) and Cell Migration Prmentioning
confidence: 99%
See 3 more Smart Citations